UMP launched UMPValid8 and Mobile Wallet UMP Xchain - Irene, Wei Kiong Ting (2018)
Universiti Malaysia Pahang has emerged as the first public university in Malaysia to use Blockchain Technology for its UMPValid8 and Mobile Wallet UMP XChain. UMPValid8 is a new application designed to validate the authenticity of degree certificates using QR Code. Specifically, each certificate will be embedded with a unique QR Code to ensure that it is original. When the QR Code is scanned, the student’s details such as picture, full name, programme and graduation year will be shown. UMP students’ education records and peronal data will be stored in this system. As a result of a collaboration between IBM Centre of Excellent (IT experts), UMP Alumni and Faculty of Industrial Management (Supply Chain experts), and Bank Muamalat (consultants), this system is planned to be used in this coming 2018 convocation ceremony.